1999
DOI: 10.1097/00003246-199909000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between mixed venous oxygen saturation and markers of tissue oxygenation in progressive hypoxic hypoxia and in isovolemic anemic hypoxia in 8- to 12-day-old piglets

Abstract: In comparison with hypoxic hypoxia, critical values of SvO2 are higher in anemic hypoxia, indicating that oxygen unloading from blood to tissues is impaired in anemic hypoxia. These characteristics in oxygen transport and capillary hemodynamics should be taken into consideration when SvO2 is used in clinical critical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…1 The mixed venous oxygen saturation (SvO 2 ) reveals the amount of residual oxygen after tissue oxygen extraction and represents the combined sufficiency of the arterial oxygen content, cardiac output, and tissue oxygen consumption. [8][9][10] Hirschl et al, 7 demonstrated that right atrial mixed venous oxygen saturation in an animal model is an excellent way of monitoring the effect of airway pressure or hypovolaemia on oxygen delivery, compared with using SaO 2 alone.…”
Section: Enous Oxygen Can Be Measured As Anmentioning
confidence: 99%
“…1 The mixed venous oxygen saturation (SvO 2 ) reveals the amount of residual oxygen after tissue oxygen extraction and represents the combined sufficiency of the arterial oxygen content, cardiac output, and tissue oxygen consumption. [8][9][10] Hirschl et al, 7 demonstrated that right atrial mixed venous oxygen saturation in an animal model is an excellent way of monitoring the effect of airway pressure or hypovolaemia on oxygen delivery, compared with using SaO 2 alone.…”
Section: Enous Oxygen Can Be Measured As Anmentioning
confidence: 99%
“…It therefore seems that lung function is more critical to oxygen delivery to the tissues than is the concentration of haemoglobin. This view is supported by an animal study (39) in which piglets with impaired lung function needed much higher oxygen concentrations in the ventilation gas than did otherwise healthy piglets with normovolaemic anaemia. Accordingly, when lung function is impaired, the organism has reduced DO 2 capacity, and the critical concentration of haemoglobin is higher than at normal lung function.…”
mentioning
confidence: 90%
“…In animal models of low CO, so‐called stagnant hypoxia, oxygen consumption quickly becomes limited by oxygen supply (supply dependence or dysoxia), highlighting the importance of CO to oxygen delivery 5–7 . An oxygen debt develops and anaerobic metabolism results in lactic acidaemia 8 …”
Section: Systemic Oxygen Deliverymentioning
confidence: 99%